Peran walisongo dalam pengembangan masyarakat jawa - Sha'af, Mohammad Adnan (Maliki Interdisciplinary Journal, 2025)
This article aims to analyze the influence of Wali Songo on the development of Javanese society, both from a spiritual, social and cultural perspective. In Javanese society, the term walisongo is a name that is very well known and has a special meaning, namely it is used to name figures who are seen as the beginning of Islamic broadcasting in Java. They are known as the nine saints who not only spread the religion of Islam, but also played a big role in developing Javanese society. Using a historical and sociological approach, this article describes how the Wali Songo preaching method was adapted to local wisdom, as well as its impact on social transformation and the formation of Javanese community identity. Their influence is not only limited to the spiritual aspect, but also touches the social, cultural, and educational realms. Until now, the legacy of Walisongo remains alive in the traditions, culture, and values ​​of Javanese society. We should be able to emulate and practice them as best we can.